مناهج البحث في دراسات الهيكل التمويلي - فاخر مفتاح بوفرنة (Scientific Journal of University of Benghazi, 2019)
This study aims to discuss the methodology mainly used in previous capital structure studies and shed more lights on the drawbacks of this methodology, in order to reach a methodology appropriate to studies of capital structure and avoid the shortcomings and shortages of prevailing traditional methodology. To achieve the aim of this study, the conceptual research methodology was adopted, in order to reach suitable methodology for capital structure studies. This study shows the historical developments of capital structure studies and illustrates how some conceptions of capital structure theory, such as, the pecking order theory and Signalling theory, and some financial and non- financial and behavioural factors, which affect capital structure decisions, can be tested. This study reveals that a systematic combination of regression analysis models and survey questionnaire for testing financial and non- financial and behavioural factors that affect firms’ capital structure may take the methodology in the mainstream capital structure studies a step further. Furthermore, it would mitigate the problem of the unavailability of “hard” data (financial statements) needed in capital structure studies in some business contexts.